MOBILE HEALTH AND ARTIFICIAL INTELLIGENCE SOLUTIONS FOR MIGRAINE MANAGEMENT- A LITERATURE REVIEW - Kinga Szyszka; Anna Baranowska; Marta Cieślak; Laura Kurczoba; Aleksandra Oparcik; Anastazja Orłowa; Anita Pakuła; Klaudia Martyna Patrzykąt; Julia Pawłowska; Kamil Turlej (International Journal of Innovative Technologies in Social Science, 2025)
Migraine is a common neurological condition that impairs patients’ function, creates substantial societal costs, causes disability, and diminishes life quality. The wide range of symptoms, triggers, and treatment responses makes migraine diagnosis and management extremely difficult. The current management strategies rely on patient-maintained diaries, which are prone to recall bias and thus not effective for accurate tracking. Digital technologies, including mobile health applications and artificial intelligence systems, now play a significant role in migraine care, and they are revolutionizing treatment approaches. The new generation of applications uses AI to process biometric and behavioral data to enhance diagnostic accuracy and support individualized treatment plans, thereby supporting both patient autonomy and clinical decision-making. This review evaluates scientific evidence on mobile applications and artificial intelligence systems that support migraine diagnosis, tracking, and treatment. Research indicates the need for randomized controlled trials to establish the clinical value and advantages of these innovative solutions.